Microbiota of the Whitefly Bemisia tabaci (Hemiptera: Aleyrodidae) by 16S rDNA Illumina Sequencing - Afef Najjari; Chahnez Naccache; Nour Abdelkefi; Salma Djebbi; Amira Souii; Brahim Chermiti; Mourad Elloumi; Maha Mezghani Khemakhem (Microbiology Research)
Bemisia tabaci (Aleyrodidae family) is one of the most damaging pests of numerous crops worldwide. Insecticides, namely pyrethroids and organophosphates, have long been the primary control tools against this pest, resulting in several resistance cases. In Tunisia, the two most damaging biotypes of B. tabaci, MEAM1-B and MED-Q, are sympatric, and more concerns about developing resistance keep rising due to the extensive use of insecticides. Here, we aimed to elucidate the molecular mechanism of resistance to pyrethroids and organophosphorus insecticides in two Tunisian populations of B. tabaci, collected respectively on Capsicum annuum and Lantana camara, and then determine the bacterial community associated with insecticide resistance and susceptible biotypes based on 16S rRNA Illumina sequencing. The results showed that the population collected on Capsicum annuum belonged to the MEAM1-B biotype with an insecticide resistance profile. In contrast, the population collected on the Lantana camara belonged to the MED-Q biotype with a sensitive profile. The bacterial communities of the two biotypes were predominantly structured by the Proteobacteria phylum and three genera, including Candidatus Portiera, the secondary facultative symbiont, and Hamiltonella, which were unevenly distributed between the two biotopes. Our results provide the first evidence for insecticide resistance alleles in Tunisian MEAM1-B populations and suggest an association between bacterial community composition within susceptible biotypes and insecticide resistance.